2020
DOI: 10.1186/s12885-020-07309-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of order with radiation therapy in stage IIIA pathologic N2 NSCLC patients: a population-based study

Abstract: Background: The aim of this study was to investigate the optimal order of radiation therapy in patients affected by stage IIIA pathologic N2 (IIIA/N2) non-small-cell lung cancer (NSCLC) and to identify its potential risk factors. Methods: 17,654 (8786 men and 8868 women) diagnosed with NSCLC stage IIIA-N2 from 2004 to 2015 patients were identified in the Surveillance, Epidemiology, and End Results (SEER) database. Among the relevant clinical parameters, we evaluated overall survival (OS), lung cancer-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Primary treatment strategies might be changing as systemic therapies develop, but some researchers have suggested that positive responses to systemic therapy would make more NSCLC patients eligible for operative management [ 18 , 26 , 27 ]. According to the Robinson classification, specific cases of N2-patients had a higher possibility of survival as a part of multimodal therapy after an operative therapy [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary treatment strategies might be changing as systemic therapies develop, but some researchers have suggested that positive responses to systemic therapy would make more NSCLC patients eligible for operative management [ 18 , 26 , 27 ]. According to the Robinson classification, specific cases of N2-patients had a higher possibility of survival as a part of multimodal therapy after an operative therapy [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A propensity score-matching analysis enrolled 3334 resected stage IIIA-N2 NSCLC patients and demonstrated that postoperative radiotherapy could only offer significantly overall survival benefits to <60 years old group (5-year OS, 35.4% for postoperative radiotherapy vs. 28.9% for no postoperative radiotherapy; p = 0.026), but not to 60–79 years old group ( p = 0.062) and >80 years old group ( p = 0.198) [ 30 ]. However, a retrospective study analyzed 17,654 stage IIIA N2 NSCLC patients and found that the surgery alone group did not have survival benefits compared to the no surgery group, and postoperative radiotherapy was recommended in patients >75 years old [ 31 ]. Another retrospective research based on 2515 stage IIIA N2 NSCLC patients showed that the survival benefits of delayed radiation after surgery was more significant in patients >60 years old (Logrank p = 0.002) compared to patients ≤60 years old (Logrank p = 0.871) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the differences were statistically significant before and after PSM in the lung SCC subgroups ( P = 0.000 and P = 0.043, respectively). More encouragingly, some studies have shown that PrORT is an independent prognostic factor of OS in patients with stage IIIA-N2 NSCLC, and there is no obvious benefit in AC [ 19–21 ]. To some extent, this is consistent with our conclusions.…”
Section: Discussionmentioning
confidence: 99%